A phase II trial of paclitaxel and epirubicin in advanced breast cancer - Rischin, D (Nature Publishing Group, 2000)
Initial trials of paclitaxel and doxorubicin in advanced breast cancer yielded high response rates but significant cardiac toxicity was observed. In this phase II trial we investigated the efficacy and safety of paclitaxel combined with epirubicin. Patients with advanced breast cancer, performance status 0–2, measurable disease, and a normal left ventricular ejection fraction, who may have received adjuvant chemotherapy were treated with epirubicin 75 mg m(–2)followed by a 3-h infusion of paclitaxel 175 mg m(–2)repeated every 3 weeks. Forty-three eligible patients were treated at six centres. 67% patients received the maximum of six cycles. The response rate was 54% (95% CI 38–69%), 12% CR and 42% PR. Estimated median progression-free survival was 6.9 months (95% CI 5.4–10.0) and estimated median overall survival was 17.9 months (95% CI 14.2–25.7). Four patients had a decrease in the left ventricular ejection fraction (LVEF) of ≥20% of baseline value, and in two patients the LVEF decreased to below the lower limit of normal, but no patient developed clinical evidence of cardiac failure. Grade 4 neutropenia occurred in 56% cycles, but only 4% of cycles were complicated by febrile neutropenia. Grade 3 or 4 non-haematologic toxicity was uncommon. In conclusion, paclitaxel 175 mg m(–2)and epirubicin 75 mg m(–2)is a well tolerated, promising regimen for the treatment of advanced breast cancer. © 2000 Cancer Research Campaign